Proceedings of the 2nd ACM Conference on Information-Centric Networking 2015
DOI: 10.1145/2810156.2810160
|View full text |Cite
|
Sign up to set email alerts
|

Consumer / Producer Communication with Application Level Framing in Named Data Networking

Abstract: Over time the Internet has evolved from a network that interconnects hosts to a network that interconnects information objects broadly defined; these objects range from movie files, Facebook content, twitter messages, to sensor data and authenticated device actuation commands.As a newly proposed architecture to meet this new usage, Named Data Networking (NDN) replaces the host-based addressing scheme by names of information objects in moving packets through the network. In an NDN network consumers send Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…NDN is a state-of-the-art new emerging technology that can effectively solve many problems caused by conventional Internet architecture [41]. NDN is an ICN application that keeps its focus on information, rather than location [42] NDN naturally solves many IP architecture problems, such as routing loop and consumer mobility [43]. The major advantage of NDN is in-network caching from the network Content Store (CS).…”
Section: Background Of Named Data Networkmentioning
confidence: 99%
“…NDN is a state-of-the-art new emerging technology that can effectively solve many problems caused by conventional Internet architecture [41]. NDN is an ICN application that keeps its focus on information, rather than location [42] NDN naturally solves many IP architecture problems, such as routing loop and consumer mobility [43]. The major advantage of NDN is in-network caching from the network Content Store (CS).…”
Section: Background Of Named Data Networkmentioning
confidence: 99%
“…An IP-based application can also implement its own transport mechanisms by following the Application-Level-Framing (ALF) concept [16]. Related work has shown that ICN can provide similar transport mechanisms to applications with CCT requirements [17][18][19]. ICT does not preclude CCT transport mechanisms for ICN applications.…”
Section: Information-centric Transportmentioning
confidence: 99%
“…The work in [17] proposes a consumer-producer API, built to simplify and reduce the implementation efforts of NDN application developers. Although this work addresses some of the challenges discussed here, we propose a general-purpose information-centric abstraction and a mechanism that provide in-network transport.…”
Section: Related Workmentioning
confidence: 99%
“…Several attempts have been made for wrapping the Interest/Data messaging into more conveniently usable primitives, the motivation being that for example "reliable and secure application-level message exchange" or "file replication" are the relevant services in which application developers are interested in. Support for Producer/Consumer communication has been the focus of several authors (Moiseenko [13], PARC's CCNx 1.0 lib and now CICN sockets [16]). ChronoSync [39] can be seen as way to automatically replicate hierarchically organized data over ICN.…”
Section: Icn Apis Beyond Interest/data Messagingmentioning
confidence: 99%